PROBLEMS AND SOLUTIONS FOR THE DEVELOPMENT OF PHYSICAL EDUCATION AND MASS SPORTS (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
The article is about the problems and solutions of Science Education in the field of physical education and sports, the study of professional educational benchmarks in physical education and sports activity of athletes, the close connection of sports federations with sports organizations in professional sports education, the formation of various sports education studies between problem situations and sports organizations of education